Integration of Fetal Middle Cerebral Arterial (MCA) Ultrasonography in Acute Fetal-Maternal Hemorrhage - Jessian L. Munoz; Maria Schleicher; Natalie Bowersox (Hindawi Limited, 2019)
Here we present a case of maternal-fetal hemorrhage characterized by intermittently reassuring fetal testing. Additional testing performed with ultrasound, including middle cerebral artery (MCA) doppler waveforms, confirmed fetal hemorrhage followed by emergent cesarean section. This report highlights the acute usage of MCA dopplers in obstetric decision making. The Newborn required transfusion but otherwise recovered well. MCA may be a useful tool for fetal assessment in Labor and Delivery units.